Three new species of the genus Tycherobius Bolland (Acari: Camerobiidae) from Iran - Khanjani, Mohammad; Yazyanpanah, Shima; Ostovan, Hadi; Fayaz, Bahman Asali (Zootaxa, 2012)
Three new species of the genus Tycherobius Bolland, 1986, Tycherobius iranensis sp. nov., Tycherobius ueckermanni sp.nov. and Tycherobius farsiensis sp. nov., collected from soil and rotten leaves under oak trees (Quercus brantii Lindl. (Fa-gaceae)) in Iran, are described and illustrated. This genus is recorded for the first time in Iran. A key to all known species is given.